Pembentukan Karakter Religius Melalui Program Gerakan Anak Pejuang Subuh Di TPQ Al Muqorrobin Panjangsari Gombong - Istiqomah, Dini; Husna, Nihayatul (Tarbi: Jurnal Ilmiah Mahasiswa, 2025)
Behind such rapid progress, the negative impact is starting to be seen, namely the decline in the noble values of religion, customs and social norms which so far have been highly respected and considered important by the Indonesian nation and are now starting to be ignored. Seeing these conditions, TPQ Al Muqorrobin Panjangsari Gombong implemented a program called the "Dawn Warrior Child Movement Program" to shape the religious character of the students. The aim of the study was to find out the description of the process and find out the results in the formation of the religious character of the students in the Subuh Warrior Children's Movement program at TPQ Al Muqorrobin. This research uses a qualitative descriptive approach. The research design is descriptive research. Data obtained from observations, interviews and documentation. Data processing techniques are using data reduction, data presentation and drawing conclusions. The results obtained in this research are: (1) The process of forming the religious character of the students in the Subuh Warrior Child Movement program is divided into several stages, including: the introduction stage, the knowledge and example stage, the awareness stage, the implementation stage, the application stage, building the image of an educational park Al-Qur'an, Mujahadah and prayer. (2) The results of the formation of the religious character of the students in the Subuh Child Warrior Movement program are: increasing faith and devotion to Allah SWT, the formation of good character or good morals, increasing the students' religious knowledge, and the students being able to apply religious values in their daily lives